The Influence Of Identity On The Intellectual Pluralism Of References In Architecture. - Ahmed Hashim Hammed El-Eqapy (Iraqi Journal of Architecture and Planning, 2017)
Contemporary proposals focused on studying the general framework of the qualitative mental effect on the concepts that generally affects in the design process, a need for studying the clear influence of one of concepts representing the ideation which itâ€™s the concept of identity from a pluralistic perspective on an important single specialty in the detailed design framework so the importance of studying intellectual pluralism of reference in Architecture by identity are clarified.  This research aims to define the general principles of the concept of ideation by reviewing a clarifying manner for representing it throw the identity to deduce the theoretical knowledge framework.  Projecting towards studying the concept of the architectural reference and reviewing specialist knowledge on the research subject to conclude the of applicable knowledge framework of it so the main problem will be subjected on ambiguity of the knowledge visualization about the effect of inspection the theoretical indicators of the identity on multi mental of the reference in the architecture and its aim by give intensive details on its effects, then applying the theoretical framework on the applicable one then view and analyze and discuss the results and exploring the verifications patterns and propose the conclusions and the final recommendations. to suggest that the references in the architecture of intellectual assets for the product of the previous architectural affected by identity and cost indicators representing a plurality of intellectual.